Two-dimensional mineral hydrogel-derived single atoms-anchored heterostructures for ultrastable hydrogen evolution - Fucong Lyu; Shanshan Zeng; Zhe Jia; Fei-Xiang Ma; Ligang Sun; Lizi Cheng; Jie Pan; Yan Bao; Zhengyi Mao; Yu Bu; Yang Yang Li; Jian Lu (Nature Communications, 2022)
It remains a great challenge to achieve large-scale fabrication of single atom-anchored heterostructured catalysts with high stability, low cost, and convenience. Here, the authors report single iron atom-dispersed Mo-based nanosheets synthesized from a scalable two-dimensional mineral hydrogel approach for hydrogen evolution reaction in alkaline condition.